Exploring Plantation Development and Land Cover Changes in the Meme-Mungo Corridor of Cameroon - Forba, Cletus Fru; Kimengsi, Jude Ndzifon (International Journal of Global Sustainability, 2021)
There is an apparent nexus between the development of plantations and changes in landcover. The Meme-Mungo Corridor is an example par excellence of a tropical plantation corridor in Cameroon which has witnessed significant expansion in tropical plantations of cocoa, banana, rubber and oil palm, among others. This paper analyzes the connection between land cover changes and plantation development over a 42-year period (1960 and 2012). A total of 100 households were sampled using the systematic sampling technique. Furthermore, multispectral data, obtained from the Global Land Cover Facility (GLCF, 2005) were used in the classification of the study area. These images were processed using Geographic Information System (GIS) and Remote Sensing (RS) software and further compiled into a GIS database using ESRI ArcGIS software. The results showed that between 1960 and 2012, a more than 50% increase in the surface area of plantation crops was registered, leadingto a corresponding change in the land cover situation. Based on this, the study probed into the implications of further plantation development on land cover; further land cover changes could be attributed to the extension of plantations. This paperrecommends among others, the need for intensive agriculture to be encouraged so as to ensure an increase in agricultural output against the backdrop of a decline in agricultural space. Furthermore, augmenting agro-product value chains will stem the loss of agro-produce due to perishability. This will contribute to regulate extensive plantation development in the area.